Comparison of Platelet-Rich Plasma, Stromal Vascular Fraction (SVF), or SVF with an Injectable PLGA Nanofiber Scaffold for the Treatment of Osteochondral Injury in Dogs - Franklin, Samuel P.; Stoker, Aaron M.; Bozynski, Chantelle C.; Kuroki, Keiichi; Clarke, Kevin M.; Johnson, Jed K.; Cook, James L. (The Journal of Knee Surgery, 2018)
Stromal vascular fraction (SVF) contains a small number of mesenchymal stem cells and has been used as a treatment for osteoarthritis and cartilage injury. Due to limited evidence of successful cartilage regeneration with injected stem cell therapies, there is interest in combining cellular therapies with injectable scaffolding materials to increase intra-articular residence times of stem cells and improve tissue regeneration. However, the safety of intra-articular injection of SVF combined with injectable scaffolds is unestablished. Also, it is unclear if SVF therapy is superior to more easily prepared biologics, such as platelet-rich plasma (PRP). The purpose of this study was to assess the safety of SVF when combined with an injectable poly(L-lactide-co-glycolide) nanofiber scaffold and to provide a comparison of SVF therapy to PRP. A total of 12 Beagles had osteochondral defects created in both medial femoral condyles and 4 dogs each were allocated to treatment groups of SVF (n = 4), SVF plus PLGA scaffolding (n = 4), or leukoreduced PRP (n = 4). One knee in each dog received treatment, and the contralateral knee was sham treated with saline. Dogs were assessed over a 6-month period, and outcome measures included functional, radiographic, biochemical, and histological assessments. PRP treatment resulted in improvements in lameness scores and objective kinetic assessments of function. There were no statistically significant improvements in function, cartilage biochemical composition, or histology for SVF-treated knees. The combination of SVF and the injectable PLGA scaffold had worse outcomes than other groups including sham treatment based upon functional, biochemical, and histological assessments, raising concerns over the safety of this scaffold for intra-articular injection.
Keywords: orthobiologics; osteoarthritis; platelet-rich plasma; stem cells; stromal vascular fraction; cartilage injury